Hubungan Faktor Sosial Ekonomi dan Proses Pengambilan Keputusan dengan Praktik Pemberian MPASI oleh Ibu Berdasarkan Teori Perilaku Konsumen di Wilayah Kerja Puskesmas Putat Jaya - Nadia Shafira Ristyaning Putri; Sri Sumarmi (Pusat riset dan Inovasi Nasional, 2026)
Inappropriate complementary feeding (MPASI) practices remain a public health concern, particularly during the first 1,000 days of life, as they contribute to the risk of growth disorders such as stunting. This study aimed to analyze the relationship between socioeconomic factors and maternal decision-making processes with complementary feeding practices based on consumer behavior theory. This study employed an observational analytic design with a cross-sectional approach involving 240 mothers with children aged 6–23 months in the working area of Puskesmas Putat Jaya, Surabaya. Data were collected through structured interviews and analyzed using the Chi-Square test. The results showed significant relationships between socioeconomic status and decision-making processes, as well as between decision-making processes and complementary feeding practices (p<0.05). Mothers with higher socioeconomic status tended to have better decision-making processes and more appropriate feeding practices. However, overall practices were not fully aligned with recommended standards. These findings indicate that improving complementary feeding practices requires not only knowledge enhancement but also strengthening maternal decision-making capacity within their socioeconomic context.